Determinants of interest in using electronic money in Indonesia: evidence from Denpasar, Bali - Kadek Kharisma Suryandari; Ni Putu Wiwin Setyari (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2020)
Electronic money has received high attention from urban people in Denpasar, Bali. However, the use of electronic money is not yet fully known in relation to what factors influence user interest.  This study aims to determine the relationship between factors that influence interest in using electronic money in Denpasar City, Bali Province. Data is obtained from online questionnaires on Google form, involve active users of Go-Pay, OVO, and Dana product. There are four variables observed including the risk perception, ease of use, benefit of use, and promotion. The research was worked with the confirmatory factor analysis. The results showed that majority of the users of electronic money are 20-25 years old, are female, have a bachelor's degree, and earn 2-4 million rupiahs. All variables show significant relationship to explains the interest in using electronic money.   Interest in using electronic money is higher when the perception of risk is low, expand transactions, increases productivity and is supported by attractive promotion.  The research suggests the attempts such as change in people's behavior to steadily use electronic money, regulation of the financial system stability to facility the use of electronic money and promotion are continuously strived so that users understand the risks and advantages of electronic money.  JEL Classification E42; G32; M30